Dandy-Walker malformation in methylmalonic acidemia: a rare case report - Jingwei Liu; Zhuohang Liu; Haibo Yan; Yumei Li (BMC, 2021)
Abstract Background Methylmalonic acidemia is an organic acid metabolism disorder that usually has nonspecific clinical manifestations. Case presentation A 3-month-old female infant was admitted to the hospital for developmental retardation. Her prenatal and birth history was unremarkable. After admission, she developed dyspnea and severe anemia and was subsequently transferred to the intensive care unit. Magnetic resonance imaging of her brain showed a Dandy-Walker malformation, and metabolic screening indicated methylmalonic acidemia. Thus, she was diagnosed with methylmalonic acidemia and Dandy-Walker malformation. The patient underwent treatment including acidosis correction, blood transfusion, antibiotics, mechanical ventilation and heat preservation. Unfortunately, her condition progressively worsened and she died of metabolic crisis. Conclusions Dandy-Walker malformation may be a clinical manifestation of methylmalonic acidemia. Additionally, the co-existence of methylmalonic acidemia and Dandy-Walker malformation may be an uncharacterized syndrome which needs to be studied further.